The Role of Spirituality Therapy Emphasizing the Teachings of Islam in Enhancing Resilience and Reducing Depressive Symptoms Among Families of Children with Autism - Abulhasanlou, Ahmad; Mokhles, Hasan (Psychological Research in Individuals with Exceptional Needs, 2026)
The present study aimed to determine the role of spirituality therapy emphasizing the teachings of Islam in enhancing resilience and reducing depressive symptoms among families of children with autism in Khoy, Iran, in 2024. In terms of its purpose, this study was applied research, and in terms of data collection, it was a field study. The study employed a quasi-experimental method with a pretest–posttest design and a control group. The statistical population comprised all families of children with autism in Khoy who attended one of the rehabilitation and educational centers for children with autism in 2024. Using purposive and convenience sampling, 30 participants were selected and randomly assigned to two groups of 15 participants each (experimental and control). Participants completed the Connor-Davidson Resilience Scale (Connor & Davidson, 2003) and the 13-item Beck Depression Inventory. Participants in the experimental group received 10 sessions of a spirituality therapy program based on Islamic teachings. The data were analyzed using multivariate analysis of covariance (MANCOVA). The results supported the research hypothesis regarding the effectiveness of spirituality therapy in improving resilience and reducing depression among families of children with autism in Khoy. At posttest, parents in the experimental group exhibited significantly higher levels of resilience and lower levels of depressive symptoms than parents in the control group. Therefore, the spirituality therapy program emphasizing the teachings of Islam was effective in enhancing resilience and reducing depressive symptoms among families of children with autism in Khoy.